Pengaruh Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Perdagangan Besar Barang Produksi Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2016 - 2018 - Burhanudin, Muhammad; Cipta, Wayan (Universitas Pendidikan Ganesha, 2021)
This study aims to examine the effect of capital structure and company size on firm value in the large trade sub sector of manufactured goods listed on the Indonesia Stock Exchange in 2016 - 2018, either simultaneously or partially. The population used in this study is the sub-sector companies of large-scale production goods listed on the Indonesia Stock Exchange which submit their financial reports of 26 companies. The design of this research is causal quantitative as proof of the effect of capital structure and firm size as independent variables on firm value as the dependent variable. The data collected by documents recording, and analyzed by multiple linear regression analysis. The results showed that: (1) capital structure and firm size had a significant effect on firm value, (2) capital structure had a positive and significant effect on firm value, (3) firm size had a negative and significant effect on firm value.